Investigating SI Skills: Methodological and didactic reflections - Schjoldager, Anne (HERMES - Journal of Language and Communication in Business, 1993)
The paper presents and discusses an empirical study of simultaneous interpreting (SI) between English and Danish, carried out with a view to improving the SI teaching situation. Since the study is still in its preliminary stages, the paper focusses on methodological and didactic reflections. One important hypothesis is that the main difference between SI and non-literary translation (herafter referred to as "translation") is to be found in transmission conditions and process rather than in objective. The paper gives the rationale of this hypothesis and, by means of examples from the empirical data, tries to examine its truth-value. For methodological and diagnostic reasons, the study concentrates on the rendition of progressive "meaning" in English and Danish. The paper explains how the subjects' mastry of progressive aspect, which is realized in very different ways in the two languages, may be used as on indicator for the communicative adequacy of their target texts (herefter referred to as TTs).